Study the Ascorbic Acid Levels, Lipoprotein Ratio and Hypocholesterolemia Action of Dry Okra Extract on Experimental Model of Locally Male Rabbits - Hamzah H. Kzar (Journal of Global Pharma Technology, 2016)
Okra (Abelmoschus esculentus) is a flowering plant in the mallow family. Okra is important for its edible green and dry seed pods. The plant is cultivated in tropical, subtropical and warm temperate regions around the world. The geographical source of okra now is very available in Iraq. The rabbit rapidly develops severe hypercholesterolemia and decrease in levels of ascorbic acid and increase in ratio of bad cholesterol to good cholesterol in response to dietary manipulation. The results of this study showed that, there was a significant decrease in serum total cholesterol  and lipoprotein ratio for groups of rabbits that administrated with dry okra aqueous extract with its seeds (0.5g/kg) (DOE+ cholesterol oil-fed) as compared to control group( not administrated) at the end of six week of experiment (398±4.0) vs. (175± 5) (P < 0.05). On the other hand, a significant difference in the level of serum total cholesterol (P<0.05) starts in control group treated with cholesterol-oil fed at the end of six week of experiment as compared to cholesterol+ DOE group  (398±4) vs. (543±4). The aqueous extract of dry okra may be enhancing the conversion of cholesterol to bile acids in the liver by activation of an enzyme α-hydroxylase. DOE may be having inhibition action on HMG-COA synthase that responsible on endogenous synthesis of cholesterol in liver. Keywords: Dry okra extract, Induce cholesterol. Lipoprotein ratio, Ascorbic acid.